JARINGAN LEMAK PUTIH DAN JARINGAN LEMAK COKLAT Aspek histofisiologi - Karundeng, Ronny; Wangko, Sunny; Kalangi, Sonny J. R. (Jurnal Biomedik : JBM, 2014)
Abstract: There are two types of adipose tissues, white adipose tissue and brown adipose tissue. White adipose tissue is distributed in subcutaneous tissues meanwhile brown adipose tissue is located in certain parts of the body, neck and interscapulaar regions, in fetus and infants. Cells of adipose tissue are named adipocytes. The adipocyte of white adipose tissue contains one lipid locus (unilocular), meanwhile the adipocyte of brown adipose tissue contains many small lipid inclusions (multilocular). In adults, all adipose tissues show similar histological features-unilocular. Albeit, in certain conditions, adipocytes of brown adipose tissues can reverse to their former features, multilocular. Each type of these adipose tissue has its own characteristic in hitological and functional aspects.Keywords: white adipose tissue, brown adipose tissue, histological characteristics, functionAbstrak: Terdapat dua jenis jaringan lemak yaitu jaringan lemak putih dan jaringan lemak coklat. Jaringan lemak putih tersebar pada jaringan subkutan sedangkan jaringan lemak coklat banyak terdapat di daerah leher dan interskapular pada fetus dan bayi. Sel jaringan lemak disebut adiposit. Pada usia dewasa, semua jaringan lemak terlihat sebagai lemak unilokuler tetapi pada kondisi tertentu jaringan lemak coklat dapat kembali ke struktur semula, yaitu multilokular. Kedua jenis jaringan lemak memiliki kekhususan sendiri baik dari aspek histologik maupun fungsional.Kata kunci: jaringan lemak putih, jaringan lemak coklat, gambaran histologik, fungsi